Organized Crime in Kosovo: A Comprehensive Analysis of Narcotics and Human Trafficking (2019-2023) - Daci, Greta (European Scientific Journal, ESJ, 2024)
Organized crime poses an imminent threat in our society, driven by the pursuit of rapid wealth and power. The path to amassing large profits in a short time leads to various criminal activities, such as drug trafficking, human trafficking, and counterfeit goods, reaching global instances. This research is mainly about the Republic of Kosovo. The intent is to analyze organized crime from 2019 to 2023, taking a comprehensive interest in drug and human trafficking. Post-war countries usually struggle with extensive criminal networks that cause internal turmoil; as seen in Kosovo. Fostering criminal cooperation and battling corruption while providing security and safety remain significant internal issues. Its favorable location along the Balkan route and a pathway to illicit activities driven by criminal groups with destination Europe. Additionally, using a mixed-method approach, the research offers a holistic perspective on the changes over the years, emphasizing key enforcement challenges. It also uncovers how criminal networks take advantage of security challenges and legislative gaps to operate freely. Furthermore, the study concludes that stricter enforcement laws and intensified anti-corruption efforts are urgently needed. Improving security policies and practices, with a focus on greater collaboration with other Balkan countries, enhancing border control, and tightening oversight in northern Kosovo are also priorities. Implementing the proposed measures would improve Kosovo’s fight against organized crime and serve as a combat model for other Balkan countries.